Attitudes and barriers to pelvic floor muscle exercises of women with stress urinary incontinence - Wilai Sawettikamporn; Sirirat Sarit-apirak; Jittima Manonai (BMC, 2022)
Abstract Background Pelvic floor muscle exercise (PFME) is a first-line treatment for stress urinary incontinence (SUI), but adherence to PFME is often problematic. The aim of this study was to better understand the attitudes and barriers to practicing pelvic floor muscle exercise among women with SUI. Methods We conducted a qualitative study using semi-structured interviews. Purposive sampling was used to approach eligible participants. The interview included questions focused on women's perceptions regarding SUI and PFME, sources of information, support, and barriers and motivators of PFME. In-depth interviews were conducted until data saturation occurred. After several readings of written interview transcripts, codes were retrieved, and thematic analysis was conducted. Results Seven women participated in the study (average age 53.2 years), and most (4/7) were retired. Three salient themes emerged from the data: (1) perception of SUI, (2) barriers to PFME, and (3) motivators to exercise. Participants highlighted various barriers to PFME: (1) lack of self-discipline owing to both intrinsic and extrinsic factors, (2) lack of confidence in how to perform the exercises properly, and (3) skepticism regarding the efficacy of treatment according to women's direct and indirect experiences. Achievement of desired outcomes, symptom severity, women's expectations, and fear of surgery were motivators to regularly perform PFME. Conclusions The main barriers to regular PFME were inadequate self-discipline, knowledge, and confidence in performing the exercises, and a poor perception about the effectiveness of PFME.